2015
DOI: 10.1007/s00775-015-1241-y
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of apoNeuroglobin with heme–Aβ complexes relevant to Alzheimer’s disease

Abstract: Heme-Aβ complexes are known to produce toxic partially reduced oxygen species (PROS), catalyze oxidation of neurotransmitters and have been associated with Alzheimer's disease (AD). Neuroglobin (Ngb) play a crucial neuroprotective role against oxidative damage, hypoxic injuries, stroke and apoptosis of neuronal cells. In this study, the interaction of heme-Aβ with apoNeuroglobin (apoNgb) has been investigated using a combination of spectroscopic techniques. Absorption and resonance Raman data confirm that apoN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 91 publications
0
20
0
Order By: Relevance
“…E2 has a neuroprotective effect in several animal models of neurodegenerative diseases, such as ischemia, AD and experimental autoimmune encephalomyelitis (EAE; Arevalo et al, 2015 ). In addition, ERα interaction with neurofibrillary tangle and NGB-Aβ complexes suggest that proteins aggregates with ERα and NGB may inhibit their functions, therefore de-regulation impairs neuroprotective effect in AD (Sun et al, 2013 ; Seal et al, 2015 ; Wang et al, 2016 ). NGB is co-expressed with ERα in specific hypothalamic regions (Hundahl et al, 2008 ; Cutrupi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E2 has a neuroprotective effect in several animal models of neurodegenerative diseases, such as ischemia, AD and experimental autoimmune encephalomyelitis (EAE; Arevalo et al, 2015 ). In addition, ERα interaction with neurofibrillary tangle and NGB-Aβ complexes suggest that proteins aggregates with ERα and NGB may inhibit their functions, therefore de-regulation impairs neuroprotective effect in AD (Sun et al, 2013 ; Seal et al, 2015 ; Wang et al, 2016 ). NGB is co-expressed with ERα in specific hypothalamic regions (Hundahl et al, 2008 ; Cutrupi et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…E2 protects H 2 O 2 -induced apoptosis in neurons (De Marinis et al, 2011 ). NGB is overexpressed in early stage of AD and forms a complex with amyloid-β peptide (Sun et al, 2013 ; Seal et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies showed an increased resistance of Ngb-overexpressing primary neurons [11] and PC12 cells [12] against Ab [25][26][27][28][29][30][31][32][33][34][35] -induced neurotoxicity. Ngb also sequesters heme from Ab-heme complexes, entailing a possible role in reducing the oxidation of neurotransmitters like serotonin [13]. Ngb interferes with Ab production in vivo, reducing Ab and Ab levels in a double-cross mouse model that overexpresses Ngb in an AD-linked background with both the Swedish (K670N/M671L) and Indiana (V717F) mutation [11].…”
mentioning
confidence: 99%
“…RNA interference technology was used to silence NGB and the results indicated that in silenced cells the NaAsO 2 -induced cytotoxicity was exacerbated, suggesting a protective role for NGB in this pathological condition. Amyloid beta (Aβ)-induced cell death was also counteracted by NGB overexpression by plasmid (pcDNA3-Ngb) transfection, as demonstrated by studies on PC12 cells [38] and, more recently, NGB has been shown to interact with heme-Aβ complexes known to catalyze oxidation of neurotransmitters and to have been associated with Alzheimer’s disease [39]. …”
Section: Neuroglobinmentioning
confidence: 99%
“…They include ATP production [45] and reactive oxygen species (ROS) generation [34,39,48]. NGB treatment was able to stabilize mitochondrial membrane potential [34] and NGB overexpression was associated with reduced mitochondrial DNA damage [50].…”
Section: Possible Mechanisms Of Ngb Neuroprotectionmentioning
confidence: 99%